2015
DOI: 10.1103/physrevlett.115.097201
|View full text |Cite
|
Sign up to set email alerts
|

All-Electric Access to the Magnetic-Field-Invariant Magnetization of Antiferromagnets

Abstract: The rich physics of thin film antiferromagnets can be harnessed for prospective spintronic devices given that all-electric assessment of the tiny uncompensated magnetic moment is achieved. On the example of magnetoelectric antiferromagnetic Cr2O3, we prove that spinning-current anomalous Hall magnetometry serves as an all-electric method to probe the field-invariant uncompensated magnetization of antiferromagnets. We obtain direct access to the surface magnetization of magnetoelectric antiferromagnets providin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
90
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 86 publications
(107 citation statements)
references
References 27 publications
(42 reference statements)
9
90
0
Order By: Relevance
“…The exchange bias in Figure S1 suggests parallel orientation between the cooling field and the AFM moments in FeMn. Recently with growing attention to AFM spintronics, it has been demonstrated that the cooling field lower than the threshold value also creates collinear alignments of AFM moments in plain AFM layers ( e.g ., Cr 2 O 3 , IrMn)2425. The threshold field is quite large for most AFMs, for example, 6 T for Cr 2 O 3 26.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The exchange bias in Figure S1 suggests parallel orientation between the cooling field and the AFM moments in FeMn. Recently with growing attention to AFM spintronics, it has been demonstrated that the cooling field lower than the threshold value also creates collinear alignments of AFM moments in plain AFM layers ( e.g ., Cr 2 O 3 , IrMn)2425. The threshold field is quite large for most AFMs, for example, 6 T for Cr 2 O 3 26.…”
Section: Resultsmentioning
confidence: 99%
“…The field-cooling process excludes isotropic effects such as substrate morphology, tunneling at grain boundaries, and domain wall motions, and reflects the anisotropic AFM order parameters. In addition, the resistance reduction cannot be ascribed to neither current-induced Joule heating nor the magnetic proximity effect (MPE) in Pt induced by the interfacial uncompensated moments in FeMn24, because the rising temperature only leads to increasing resistance (Fig. 1a), while the MPE generally causes at most several-Ohm shift of the total resistance (Supplementary Figure S4).…”
Section: Resultsmentioning
confidence: 99%
“…[29][30][31][32][33][34][35][36] Given the growing interest in metallic AFs, 37 another natural question is whether they are capable of generating efficient spin currents through the direct spin Hall effects, as predicted by Onsager reciprocal relations. We recently confirmed large spin current generation from such metallic AFs, in particular PtMn, through ST-FMR experiments.…”
Section: Antiferromagnets: Materials Of Interestmentioning
confidence: 99%
“…Alternatively, the AFM domain state can be detected through the anomalous Hall effect in a thin non-magnetic control gate. 28 Since the domain wall should fit inside the bit, its width d sets a limitation for the downward scaling of the length of the MEAF element. The width of this element, however, can be significantly smaller.…”
mentioning
confidence: 99%